1997
DOI: 10.1515/cclm.1997.35.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase N and Creatine Kinase-MB Isoforms in Acute Myocardial Infarction

Abstract: Summary: The aims of our study were to evaluate the plasma Carboxypeptidase N activity in normal subjects and in patients with acute myocardial infarction and to delineate its relationship with creatine kinase-MB isoforms in monitoring of acute myocardial infarction, Carboxypeptidase N being the major determinant of creatine kinase isoform conversion in plasma. The study was carried out in 34 healthy subjects and 19 patients with acute myocardial infarction diagnosed according to the World Health Organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…A few years ago, van Hensbergen et al showed that in both malignant effusions and intratumoral fluid, as well as in plasma, there is increased aminopeptidase N activity which correlates with tumor load, suggesting that this enzyme may be originating from tumor cells . Similar observations for carboxypeptidase N activity increase in myocardial infarction have also been published by Zaninotto et al Thus, as Villanueva et al suggest, there is a chance that what they see may correlate with exoprotease activities originating from tumors.…”
supporting
confidence: 80%
“…A few years ago, van Hensbergen et al showed that in both malignant effusions and intratumoral fluid, as well as in plasma, there is increased aminopeptidase N activity which correlates with tumor load, suggesting that this enzyme may be originating from tumor cells . Similar observations for carboxypeptidase N activity increase in myocardial infarction have also been published by Zaninotto et al Thus, as Villanueva et al suggest, there is a chance that what they see may correlate with exoprotease activities originating from tumors.…”
supporting
confidence: 80%
“…[39][40][41][42][43][44][45] Heightened activity of AMPN has been reported for cancer patients, 46 and CBPN activity is increased after myocardial infarction. 47 The proteins that were identified here also indicate some specificity in the cleavage patterns, i.e., the abundances of the plasma peptides observed here do not mirror the abundant proteins (see Table 2). In this data set, only one fragment was identified from serum albumin.…”
Section: Resultsmentioning
confidence: 99%
“…Serum levels of CPN2 were not investigated in patients with stroke, but increased concentrations were found in patients with acute myocardial infarction (41). For FXII, studies showed high concentrations in patients with chronic cerebrovascular diseases (42), and FXII inhibition, as well as FXII deficiency improved outcome in experimental IS (45)(46)(47)(48)(49).…”
Section: Review Of the Literature And Integrative Evaluationmentioning
confidence: 99%